An Analysis on Students’ Listening Activities as Extramural English - Nurhasela, Nurhasela; Marleni, Lusi; Asilestari, Putri (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to find out students’ listening activities of the second semester students of English Language and Education Study Program for the 2022/2023 academic year. This research is qualitative research with the research subjects were second semester students of English Language and Education Study Program at University of Pahlawan Tuanku Tambusai. The research instrument was a questionnaire and interview with qualitative analysis techniques. Based on the data analysis, the results of the analysis on students' listening activities as Extramural English were playing video games, watching TV, listening to song or music, watching movie and using internet. Therefore, the researcher concluded that most of students have listening activities as Extramural English.